Concurrent occurrence of primary mesenteric hydatid cyst with multiple calcified splenic granulomas: A rare presentation - Ravikanth Reddy (Apollo Medicine)
Hydatid cysts most commonly present in the liver and the lungs; however, they can appear more rarely in other locations, such as the mesentery, with a rather unclear mechanism of manifestation. Herein, a case of the simultaneous presence of hydatid cysts in the mesentery and multiple splenic calcified granulomas in a 62-year-old elderly man has been presented that was managed surgically by pelvic mesenteric cyst deroofing and subtotal cystectomy.